Identification of Policy Indicators for Changing Transportation Modes to Reduce Environmental Pollution in the Iran - Fadakar Masouleh , Amir; Eyzadpanah , Norouz; Jabbari , Samad (Management Strategies and Engineering Sciences, 2024)
This study aims to identify and validate key policy indicators to facilitate the transition from conventional transportation modes to sustainable alternatives, with the goal of reducing environmental pollution in Iran. A qualitative approach was employed using the fuzzy Delphi method to achieve expert consensus on the critical dimensions and indicators of sustainable transportation policies. The study engaged 20 experts, including university professors and senior professionals from the transportation and environmental sectors, selected through purposive and snowball sampling methods. Data collection involved semi-structured interviews, and the analysis focused on coding and triangulation to identify relevant policy dimensions. Triangular fuzzy sets (l, m, u) were used to quantify expert opinions and address uncertainties, ensuring the reliability of the findings. The study identified six key dimensions for effective policymaking: the role of policymakers, policy approaches, mechanisms for creating dynamism, policymakers' capabilities, mastery of environmental conditions, and the provision and utilization of necessary data. Specific indicators under these dimensions include evidence-based policymaking, participatory approaches, collaboration with academic and professional experts, integration of reliable data, and alignment with contemporary scientific paradigms. The findings emphasize the importance of institutional frameworks, systematic approaches, and stakeholder engagement in fostering sustainable transportation systems. The proposed indicators achieved consensus among experts, with fuzzy scores exceeding the threshold for validation. The results provide a comprehensive framework for developing sustainable transportation policies that address environmental challenges. The identified dimensions and indicators align with global best practices and offer actionable insights for policymakers. By emphasizing participatory and evidence-based approaches, the findings can guide national efforts to reduce environmental pollution through the promotion of sustainable transportation modes.